Inpatient therapy profile for coronary heart disease patients at Universitas Indonesia Hospital - Khoirun Nisak; Retnosari Andrajati; Atika Wahyu Puspitasari (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Coronary heart disease (CHD) was the second-highest cause of death in Indonesia. West Java is one of the provinces with a high prevalence of heart disease in Indonesia. Objective: This study aimed to determine the inpatient therapy profile for CHD patients at Universitas Indonesia Hospital (RSUI). Methods: This study was a descriptive study using data from medical records of inpatients with CHD who were registered as BPJS Kesehatan participants at RSUI from January to September 2024. Results: The results showed that 84 patients met the inclusion and exclusion criteria from a total study population of 208 patients, with the majority of patients being male (59,5%), aged <60 years (56,0%), and having a primary complaint of chest pain (79,8%). Based on laboratory characteristics, most patients had normal troponin T levels (86,9%), normal blood creatinine levels (54,8%), and random blood glucose levels <200 mg/dL (77,4%). The length of hospitalization was ≤5 days (82,1%) with improved clinical outcomes (97,6%). Most patients had ≥3 comorbidities (53,6%), with the most common comorbidities being HHD (38,1%), hypertension (35,7%), and CHF (33,3%). In addition, most patients received  ≥5 drugs (97,6%), with the commonly used therapeutic profiles being platelet aggregation inhibitors (79,8%), HMG CoA reductase inhibitors (78,6%), organic nitrates (67,9%), selective beta-blocking agents (56,0%), and ACE inhibitors (45,2%). Conclusion: The predominant therapeutic profile of CHD inpatients at RSUI included platelet aggregation inhibitors, HMG CoA reductase inhibitors, organic nitrates, selective beta-blocking agents, and ACE inhibitors.